Effective communication the helping interview - Freebairn, Janet; Concept Media, inc. (Irvine, CA : Concept Media, 2003)
Part 1 discusses warmth, genuiness, openness, and empathy as necessary interviewing qualities. Pt. 2 focuses on opening the interview and the use of questions and silence. Pt. 3 illustrates general skills of selective responding and focusing and describes ways to close the interview.
Pt. 1. Basic components, helper qualities, and attending skills (19 min.) -- pt. 2. Opening, questioning and use of silence (21 min.) -- pt. 3. Responding and closing (21 min.).
DVD
English
No Masters.
Keywords: Communication in nursing; Nurse and patient